A phase I, randomized study to evaluate the safety, tolerability, and pharmacokinetics of mefunidone in healthy subjects - Han, Mai; Huo, Bishan; Hu, Gaoyun; Zhang, Xin; Cui, Gang; Wu, Wei; Mi, Na; Zhang, Shixi; Jin, Jiangli; Lu, Xing; Wu, Bidong; Xiao, Chunyan; et al. (Frontiers in Pharmacology, 2024)
Background Mefunidone is a novel synthetic compound and is better when compared to pirfenidone for the anti-fibrotic treatment of renal fibrosis in end-stage renal disease. We conducted this first-in-human, phase I clinical trial to determine the safety, tolerability, and pharmacokinetic (PK) (including food effect) profiles of mefunidone administered orally as single and multiple ascending doses in healthy subjects. Methods Part A assessed single ascending doses of mefunidone from 25 mg to 800 mg or placebo once daily in the fasting state. Part A also assessed the effect of food on tolerability and PK in the 100 mg cohort. Part B consisted of three treatment groups who received 100 mg, 200 mg, or 400 mg of mefunidone or placebo twice daily (BID, bis in die) on days 1–6 and once in the morning on day 7. Results Single oral doses of mefunidone up to 800 mg and multiple doses of mefunidone up to 400 mg BID were all well-tolerated. Mefunidone behaved with ideal dose proportionality within the single-dose range of 50 mg–600 mg and the multiple-dose range of 100 mg BID to 400 mg BID by day 7. High-fat fed conditions led to a delay in Tmax by approximately 1 h and a slight reduction of approximately 20% in Cmax compared to that in fasting conditions, but it did not significantly affect systemic exposure. Conclusion Mefunidone exhibited favorable pharmacokinetics and safety profiles. The present study informed and supported further developmental clinical studies of mefunidone. Clinical Trial Registration clinicaltrials.gov, identifier CXHL1900206